Effects of cold and warm rolling on the shape memory response of Ni50Ti30Hf20 high-temperature shape memory alloy. (15th September 2018) - Babacan, N.; Bilal, M.; Hayrettin, C.; Liu, J.; Benafan, O.; Karaman, I.
Abstract: The present work reveals the effects of cold and warm rolling on the shape memory response and thermomechanical cyclic stability of Ni50 Ti30 Hf20 high-temperature shape memory alloy (HTSMA). Cold rolling without intermediate annealing was performed up to the maximum possible thickness reduction before surface cracks appeared. These samples were subsequently annealed at various temperatures. 550 °C was determined to be the optimum annealing temperature for 30 min durations based on the differential scanning calorimetry (DSC) and microhardness test results. Isobaric thermal cycling experiments were conducted under different constant tensile stresses. The effects of warm rolling at different temperatures and thickness reductions on the resulting recoverable transformation strains, residual strains, transformation temperatures, and thermal hysteresis were also evaluated. It was shown that the rolling led to an increase in the resistance against defect generation accompanying martensitic transformation in the present HTSMA, resulting in a significant improvement in dimensional stability during thermal cycling. The results revealed that 15% cold rolling followed by the 550 °C 30 min annealing condition showed the best actuation response, exhibiting comparable recoverable transformation levels to the hot extruded samples, with much lower residual strains. All warm rolled samples exhibited notable two-way shape memory effect (TWSME) with compressive two-way shape memory (TWSM) strains, pointing out the existence of compressive internal stress storage following warm rolling. While transformation temperatures of all rolled samples were lower than those of the starting hot extruded sample, thermal hysteresis was notably higher in the rolled samples. This was attributed to the increase in dislocation density and the change in the martensite microstructure with rolling. The present study demonstrates that NiTiHf HTSMAs that have attracted recent interest in high-temperature applications can be processed by using conventional rolling methods while preserving desired cyclic shape memory response. Graphical abstract: Image 1